IPO Studies: The Effect of Corporate Governance Structure on Underpricing With Underwriter Reputation as a Moderating Variable - Dara Audina; Sri Kurnia; Raja Yulianita Sarazwati; Chartady, Rachmad; Marina Lidya (Basic and Applied Accounting Research Journal, 2024)
The purpose of this study is to determine the influence of corporate governance structure on underpricing in companies that conduct Initial Public Offering (IPO) on the Indonesia Stock Exchange, as well as to determine the reputation of underwriters moderating the influence of corporate governance structure on underpricing. The research method used is quantitative method. The population in this study was 218 companies and the sample obtained after using purposive sampling was 167 companies. Data analysis techniques in this study are descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis test using EViews 12 software. The results of this study show that the size of the board of commissioners has a negative and significant effect on underpricing. Meanwhile, the independence of the board of commissioners and institutional ownership do not have a significant effect on underpricing in companies that conduct an Initial Public Offering (IPO) on the Indonesia Stock Exchange. It can be concluded that the reputation of the underwriter is unable to moderate the influence of the size of the board of commissioners, the independence of the board of commissioners, and institutional ownership on underpricing. In addition, an Adjusted R-squared value of 0.078222 means that 7.82% of the underpricing rate is influenced by the size of the board of commissioners, the independence of the board of commissioners, institutional ownership, and the reputation of underwriters, while the rest is influenced by other variables that are not included in this study.